Directing Self‐Assembly of Nanoscopic Cylindrical Diblock Brush Terpolymers into Films with Desired Spatial Orientations: Expansion of Chemical Composition Scope. Issue 4 (17th December 2013) - Cho, Sangho; Yang, Fan; Sun, Guorong; Eller, Michael J.; Clark, Corrie; Schweikert, Emile A.; Thackeray, James W.; Trefonas, Peter; Wooley, Karen L.; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Diblock brush terpolymers (DBTs) with different fluorinated methacrylate‐based block segments are synthesized through sequential ring‐opening metathesis polymerizations and are used to prepare polymer thin films with predictable film thicknesses. These DBTs exhibit preferable substrate vertical alignments within the films, induced by the relatively lower surface energy of the fluorinated structural components, together with the overall cylindrical morphology of the brush architecture. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>